Evaluation of a third-location decompression program for Canadian Forces members returning from Afghanistan. - Garber BG; Zamorski MA; Garber, Bryan G; Zamorski, Mark A (Military Medicine, 2012)
Background: Service members returning from combat can experience difficulty adapting to home life. To help ease this transition, the Canadian Forces provides a Third-location Decompression (TLD) program in Cyprus to members returning from deployment to Afghanistan.Methods: The 5-day program consists of individual free time, structured recreational activities, and educational programming. Its perceived value and impact were measured immediately afterward and 4 to 6 months later.Results: Respondents overwhelmingly supported the TLD concept, with 95% agreeing that "some form of TLD is a good idea." Eighty-one percent of participants found the program valuable, and 83% recommended it for future deployments to Afghanistan. Perceived value persisted 4 to 6 months after return, and 74% felt that it helped to make reintegration easier for them.Conclusion: Canadian Forces members saw value in the TLD program, and most members believed that the program had its intended effect of making the reintegration process easier for them.